2021
DOI: 10.1088/1755-1315/788/1/012128
|View full text |Cite
|
Sign up to set email alerts
|

The weight and hatchability of quail egg viewed from the weight, index, and surface area of the egg

Abstract: The research objective was to determine the weight and hatchability of quail eggs which were influenced by the weight, index, and surface area of the eggs. Quail eggs were obtained from Slamet Quail Farm, Sukabumi. The experimental design used was CRD. The treatments consisted of 3 categories, namely light egg weight (≤11.20 g), medium (11.21–13.06 g), and heavy (≥13.07 g); oval egg shape index (≤74.72), normal (74.73–84.04), and round (≥84.05); and the surface area of eggs is narrow (≤89.22 cm2), medium (89.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Several factors that might determine the success of the hatching process include egg weight and egg shape index. Study on the effects of egg weight and egg shape index on hatching performance is widely available in commercial poultry, such as chickens, ducks, and quails (Ipek and Sozcu, 2017;Iqbal et al, 2017;Kostaman and Sopiyana, 2021). However, the available body of knowledge indicating a controversy regarding the effect of egg weight and egg shape index on hatching performance.…”
Section: Journal Of Animal Health and Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors that might determine the success of the hatching process include egg weight and egg shape index. Study on the effects of egg weight and egg shape index on hatching performance is widely available in commercial poultry, such as chickens, ducks, and quails (Ipek and Sozcu, 2017;Iqbal et al, 2017;Kostaman and Sopiyana, 2021). However, the available body of knowledge indicating a controversy regarding the effect of egg weight and egg shape index on hatching performance.…”
Section: Journal Of Animal Health and Productionmentioning
confidence: 99%
“…In some studies, egg weight and egg shape index provide significant impact on hatching performance (Alasahan andCopur, 2016: Khalil et al, 2016;Ipek and Sozcu, 2017;Iqbal et al, 2017;Hegab and Hanafy, 2019). However, other studies reported negligible effect of these traits on hatching performance (Sarı et al, 2010;Onbaşılar et al, 2011;Ramaphala, 2013;Rashid et al, 2013;Kostaman and Sopiyana, 2021). Furthermore, the investigation of this topic in swiftlet is currently still very limited.…”
Section: Journal Of Animal Health and Productionmentioning
confidence: 99%
“…It is well known that quail breeding in Egypt has become very important due to some advantages over other domesticated species ( Kostaman and Sopiyana, 2021). Interestingly, Hussain et al (2019) reported that Japanese quails are small birds and can gain more than 170 grams of weight in just 28 days and can lay more or less 300 eggs per year.…”
Section: Introductionmentioning
confidence: 99%